Expectations of privacy and trust: examining the views of IT professionals. Issue 6 (2nd June 2016) - Martin, Nigel; Rice, John; Martin, Robin
Abstract : The growth of interactive online lifestyles and social networks has arguably left IT users more exposed to privacy breaches. While governments continue to revise privacy legislation, the issue of online business relationships and privacy expectations remain contentious. Indeed, fewer studies have explored the expectations of users who willingly and knowingly engage in online activities that carry privacy risks. In this study, we examine the expectations and attitudes towards online privacy of a select group of 102 IT professionals. Using a qualitative survey, we show that these users have expectations of online privacy, particularly securing and protecting information from unknown third parties. Unfortunately, these expectations may go unsatisfied with third-party monitoring enabling information disclosure. In response, users argue that enhanced technical and complementary administrative measures should be actively pursued to improve privacy outcomes. The article builds further understanding of privacy expectations and trust behaviours, while exposing the importance of technical credibility from the online organisation and user perspectives.